PERLINDUNGAN HUKUM BAGI ANAK YANG MENGALAMI KEKERASAN DALAM RUMAH TANGGA - Indah Sari (JURNAL MITRA MANAJEMEN, 2014)
AbstractLegal protection of children is rights that must be owned by children. This has been confirmed in UnitedNations conference on children’s rights in 1989, that the child has a right to be protected by their families,communities and even by nations. In reality, children don’t get protection, the opposite happens isviolence against the children. Ironically, the violence was committed by their parents. Indonesia hasmany regulations to provide the legal protection of children. Law number 23 in 2002 about the protectionof children and the Law number 23 in 2004 about the elimination of domestic violence has been set uplegal protection for children who are have experience violencing. Both laws can not be run due to manyfactors because children abuse happens at home. Among them is a factor in family poverty, socialpressures in society, the wrong meaning in understanding ownership of children, children’s obedience totheir parents, low parental education, lacl of awareness of the legal parent to provide legal protection fortheir children, so the children can not grow up with develop properly and reasonable.Key Words: Children, Rights of Child, Domestic Violence , Legal Protection of Children.